2022
DOI: 10.3389/fphar.2022.979451
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of glycoalkaloids from Solanum plants: A review

Abstract: Cancer is still one of the main causes of death worldwide. For this reason, new compounds that have chemotherapeutic potential have been identified. One such group of substances is Solanaceae glycoalkaloids (GAs). They are natural compounds produced by plants widely used in traditional medicine for healing many disorders. Among others, GAs exhibit significant antitumor properties, for example, a strong inhibitory effect on cancer cell growth. This activity can result in the induction of tumor cell apoptosis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…The distribution of glycoalkaloids across plant species is influenced by genetic factors, environmental conditions, plant development stages, and postharvest practices [15]. The most common GA found in food plants are α-solanine and α-chaconine in potato, α-tomatine in tomato, and solamargine and α-solanine in eggplants [13,16].…”
Section: Food Glycoalkaloids: Toxic Compounds In Our Daily Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of glycoalkaloids across plant species is influenced by genetic factors, environmental conditions, plant development stages, and postharvest practices [15]. The most common GA found in food plants are α-solanine and α-chaconine in potato, α-tomatine in tomato, and solamargine and α-solanine in eggplants [13,16].…”
Section: Food Glycoalkaloids: Toxic Compounds In Our Daily Foodsmentioning
confidence: 99%
“…The aglycone is derived from cholesterol and can be solasodine, solanidine, or tomatidine depending on the plant source. The oligosaccharide can vary in length and composition but usually contains glucose, galactose, rhamnose, or xylose units [15]. The glycoalkaloids are named according to their aglycone and oligosaccharide structure (Figure 1).…”
Section: Food Glycoalkaloids: Toxic Compounds In Our Daily Foodsmentioning
confidence: 99%
“…However, a recent investigation revealed that potato glycoalkaloids had little apoptotic activity and a cytotoxic impact comparable to other cancer medications. Moreover, studies have documented the anti-cancer properties of additional substances such as potato lectin and potato protease inhibitors 1 and 2 [85] .…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…For the present study, researchers reviewed studies that looked at the anticancer properties of solanine, chaconine, solasonine, solamargine, and tomatine, which are found in the nightshade family including tomatoes and potatoes (Winkiel et al, 2022). Therefore these important substances, important in human nutrition must be clearly identified and should be intend to breed cultivars with improved nutritional/ therapeutic attributes through conventional and molecular breeding approaches…”
Section: Tomato Breeding For Therapeutic/nutraceutical Formulationsmentioning
confidence: 99%